The Effectiveness of Extended Reality on Students’ Academic Performance and Motivation in Primary School Education: A Meta-Analysis (2019-2022) - Alharbi, Amal Yahya; Alazwari, Dina Mohammed; Almandeel, Kholod Kheled; Alfarani, Leena Ahmad (Journal of Educational and Psychological Sciences, 2023)
This study conducted a meta-analysis of (75) studies, published between the years 2019 to 2022, which was surveyed during the study in 2022. Furthermore, (28) studies were included as the sample for the study. This meta-analysis study was aimed to analyze the impact of Extended Reality (XR) on students’ academic performance, and motivation in the Primary Education Phase. The result of the meta-analysis, showed that the XR Technology, highlighted its importance in the educational process, as it achieved its effectiveness in academic performance and motivation. The result also identified Augmented Reality)AR(and Virtual Reality (VR(technology, as having a large effect on students’ academic performance. In addition, the study showed that students’ motivation in applying AR, is higher than in the VR. In conclusion, the research also provided a future research plan for XR-based education, including using diverse techniques that support the educational process and developing curricula based on AR and VR technologies, and recommending the need to conduct further studies on the effectiveness of virtual reality in elementary school and the effectiveness of XR technology among elementary school students on different variables in their sample.